Herbicidal Activity of Flavokawains and Related trans-Chalcones against Amaranthus tricolor L. And Echinochloa crus-galli (L.) Beauv. - Chotsaeng, Nawasit; Laosinwattana, Chamroon; Charoenying, Patchanee (My University, 2019)
Flavokawains have a broad spectrum of biological activities; however, the herbicidal activity of these naturally occurring chalcones has been less investigated. Flavokawains and their analogues were prepared by the Claisen-Schmidt condensation reaction between xanthoxyline (or aromatic ketones) and a variety of aromatic and heteroaromatic aldehydes. These compounds were then evaluated for their inhibitory effect against representative dicot and monocot plants. Among 45 synthetic chalcones, derivatives containing phenoxyacetic acid, 4-(N,N-dimethylamino)phenyl, N-methylpyrrole, or thiophenyl groups inhibited the germination and growth of Chinese amaranth (Amaranthus tricolor L.) with moderate to high degrees compared to commercial butachlor. For barnyardgrass (Echinochloa crus-galli (L.) Beauv.), most of the thiophenyl chalcones interrupted shoot and root emergence. This finding highlighted the importance of functional groups on the herbicidal activity of chalcones. The level of inhibition also depended on the applied concentrations, plant species, and plant organs. (E)-2-(2-(3-Oxo-3-(thiophen-2-yl)prop-1-enyl)phenoxy)acetic acid (14f) was the most active compound among 45 derivatives. This chalcone could be a promising structure for controlling the germination and growth of weeds. The structure-activity relationship results provide useful information about the development of active chalconoids as novel natural product-like herbicides.